Mass shootings and civilian armament - Anisin, Alexei (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"Mass Shootings and Civilian Armament provides the first comprehensive multi-methodological analysis of the relationship between mass shootings and firearm purchases (as proxied by background checks) in the US on national level data from 1999-2020. Interdisciplinary in nature, Mass Shootings and Civilian Armament will not only be of great interest to scholars of Criminology, but will also speak to Sociologists, Economists, Public Policy scholars, Political Scientists, Historians, as well as Cultural Studies and American Studies scholars"--
Introduction, How Mass Shootings Spur Gun Purchases -- Why the Current Era of Gun Culture Differs from the Past -- Case Studies, Processes, and Causal Mechanisms -- Descriptive Trends in Background Checks and Mass Shootings -- Quantitative Analysis of Mass Shootings and Background Checks, 1999-2020 -- A Configurational Analysis of Mass Shootings and Background Checks -- Looking Ahead, Has a Ceiling Been Reached?
OCLC-licensed vendor bibliographic record.
Keywords: Mass shootings -- United States; Firearms ownership -- United States; Gun control -- United States; Firearms -- Law and legislation -- United States; SOCIAL SCIENCE / Violence in Society; POLITICAL SCIENCE / Public Policy / General